Dexamethasone Intravitreal Implant (Ozurdex) for Long-Term Macular Edema after Epiretinal Membrane Peeling Surgery. (10th December 2018) - Chang, Yo-Chen; Liu, Pei-Kang; Kao, Tzu-En; Wu, Horng-Jiun; Cheng, Kai-Chun; Chen, Kuo-Jen; Wu, Kwou-Yeung; Wu, Wen-Chuan
Abstract : Purpose . To investigate the functional and anatomical outcome of the 0.7 mg dexamethasone (Ozurdex) intravitreal implant (IVD) in eyes with long-term macular edema after macular epiretinal membrane removal. Methods . We enrolled 40 eyes with persistent macular edema at least 12 months after epiretinal membrane removal. Twenty eyes in the IVD group received IVD and the other 20 eyes were in the control group. The main outcome measures were change in best-corrected visual acuity (BCVA) and central foveal thickness (CFT). Results . For eyes in the IVD group, the mean BCVA improved by 3.45 lines to 0.47 logMAR one month after IVD. However, the mean BCVA improved by only 0.14 lines to 0.74 logMAR at the same time in eyes in the control group. Six months later, the mean BCVA improved to 0.31 and 0.74 logMAR in the IVD and control groups, respectively. In the IVD group, the mean CFT decreased rapidly by 116.8  μ m to 333.9  μ m one month after IVD. Thereafter the CFT decreased at a slower pace. In the control group, the CFT remained static during the follow-up period. However, in the IVD group, 6 months after IVD, the CFT seemed to have a tendency to increase. Conclusions . Single IVD could significantly decrease macular edema and improve visual outcome for eyes with persistent long-term macular edema after macular ERM removal and the effect can be sustained as long as 6 months after the initial injection. However, in order to maintain the visual and anatomical outcome, repeat IVD might be considered if macular edema recurs.